Effect of Physics Inquiry Learning with Low-cost Experiment Tool on Students’ Problem-solving Skills and Self-efficacy - Rizki, Iqbal Ainur; Khoir, Ermia Fadilata; Nikmah, Fatihatun; Prahani, Binar Kurnia; Hariyono, Eko (Faculty of Science and Education, UIN Walisongo Semarang, 2024)
The low problem-solving skills and self-efficacy of students in physics learning significantly impact their overall learning processes and outcomes. In order to address this issue, an inquiry learning model was implemented, along with the low-cost experiment tool. This learning model is designed to be valid and effective in enhancing students' problem-solving skills and self-efficacy. The research followed a non-equivalent control group design and involved 66 students to ensure the development of a high-quality learning model that meets the required standards and criteria. By utilising learning instruments, such as students' response questionnaires, problem-solving pre- and post-tests, and self-efficacy questionnaires, the focus of the physics topic in this research was the simple mathematic pendulum. The validity test results show that the learning instrument has high validity and reliability criteria, making it feasible to use in physics learning. Furthermore, the statistical effectiveness test results show that this learning model is effective in improving students' problem-solving skills and self-efficacy. As students engage in hands-on investigations and collaborate on meaningful projects, they are prompted to apply critical thinking and decision-making skills, directly contributing to the development of effective problem-solving strategies. The intrinsic motivation derived from successfully navigating the challenges of inquiry learning, coupled with the personal relevance of the content, nurtures students' confidence in their abilities, ultimately strengthening their self-efficacy as independent and capable learners. Research implies the development of innovative learning models, effectively enhancing students' PSS and SE.